2018
DOI: 10.3390/s18041206
|View full text |Cite
|
Sign up to set email alerts
|

“What Is a Step?” Differences in How a Step Is Detected among Three Popular Activity Monitors That Have Impacted Physical Activity Research

Abstract: (1) Background: This study compared manually-counted treadmill walking steps from the hip-worn DigiwalkerSW200 and OmronHJ720ITC, and hip and wrist-worn ActiGraph GT3X+ and GT9X; determined brand-specific acceleration amplitude (g) and/or frequency (Hz) step-detection thresholds; and quantified key features of the acceleration signal during walking. (2) Methods: Twenty participants (Age: 26.7 ± 4.9 years) performed treadmill walking between 0.89-to-1.79 m/s (2–4 mph) while wearing a hip-worn DigiwalkerSW200, O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 42 publications
1
57
0
Order By: Relevance
“…Albeit being an obvious limitation, studies have shown that individuals to a large extent maintain their relative ranks within the population over time 8,9 . Furthermore, accelerometers have been shown to underestimate daily steps in frail older individuals, 29 potentially understating the amount of physical activity most beneficial for health in these populations 30 . Lastly, we only investigated associations between daily steps and all‐cause mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Albeit being an obvious limitation, studies have shown that individuals to a large extent maintain their relative ranks within the population over time 8,9 . Furthermore, accelerometers have been shown to underestimate daily steps in frail older individuals, 29 potentially understating the amount of physical activity most beneficial for health in these populations 30 . Lastly, we only investigated associations between daily steps and all‐cause mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the step-counting algorithms provided by various manufacturers are all proprietary and use different thresholds of acceleration to detect a step, which limits the comparability among studies using different devices. 73 Despite numerous validation studies showing that most commercially available accelerometers are more or less equal in general populations with normal gait, 74,75 other studies have reported that step-counting accuracy deteriorates in patients with chronic conditions, particularly during slower gait speeds. 58,76 As such, steps can still remain a useful self-monitoring metric for patients but should be avoided by researchers striving for high accuracy and reproducibility of their findings.…”
Section: Physical Activity Metricsmentioning
confidence: 99%
“…For these monitors, bias was close to zero, indicating that they were producing similar results, and the 95% limits of agreement were small, suggesting that the hip-worn monitors could be used as an alternative to measure steps. Additionally, there were similar patterns in tri-axial counts, especially on the vertical axis where steps are calculated in the ActiLife step-counting algorithm [ 1 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the most commonly used activity monitor brands in physical activity research, ActiGraph has developed multiple generations of activity monitors [ 19 ]. Researchers have validated different ActiGraph activity monitors—including GT3X vs. GT1M [ 4 ], GT1M, GT3X, vs. GT3X+ [ 20 ], and recently, GT3X+ vs. GT9X [ 21 ]—placed at different sites such as hip vs. wrist [ 15 , 22 , 23 ] during various physical activities. Although a hip placement site has been validated as an ideal location for accurately measuring steps and physical activity level in regular physical activities [ 15 ], the evaluation of multiple placement sites (hip vs. wrist) in exergaming research is needed as more upper limb movements (unlike most regular physical activity) are required for exergaming [ 8 ].…”
Section: Introductionmentioning
confidence: 99%